2001
DOI: 10.1017/s0263967x00033991
|View full text |Cite
|
Sign up to set email alerts
|

Hormone and metabolite profiles as well as the onset of ovarian cyclicity in dairy cows suffering from various forms of ketosis

Abstract: The involvement of adrenocortical and thyroid hormones in the pathogenesis of ketosis as well as the ovarian consequences of this metabolic disorder were studied in ≥2 parity cows (n=199) in 3 large scale dairy herds. To compare the plasma / serum concentrations of certain hormones [Cortisol, thyroxin (T4), triiodo-thyronine (T3), insulin, isulin-like growth factor-1 (IGF-l)J and metabolites [glucose (G), acetoacetic acid (ACAC), βOH-butyrate (BHB), non-esterified fatty acid (NEFA), trigliceride (TG), total ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…As expected on the basis of paired selection of cows in our study, metabolic parameters showed no relevant differences between groups. This indicated that there was no underlying metabolic cause that could interfere with cortisol concentrations [39] or adrenal response capacity [40]. O'Driscoll et al [41] have compared the metabolic status of cows with and without sole ulcers and found no difference in glucose, urea, and creatine-kinase concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…As expected on the basis of paired selection of cows in our study, metabolic parameters showed no relevant differences between groups. This indicated that there was no underlying metabolic cause that could interfere with cortisol concentrations [39] or adrenal response capacity [40]. O'Driscoll et al [41] have compared the metabolic status of cows with and without sole ulcers and found no difference in glucose, urea, and creatine-kinase concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…NEFA is used for energy purposes and is a precursor for the synthesis of BHB in the hepatocytes (Guo et al, 2008). Cows with high values of BHB have lower reproductive capacity, significant loss in body condition, produce a small amount of milk and suffer from extreme metabolic changes (Kessel et al, 2008, Huszenicza et al, 2006. Cows with high values of BHB have lower reproductive capacity, significant loss in body condition, produce a small amount of milk and suffer from extreme metabolic changes (Kessel et al, 2008, Huszenicza et al, 2006.…”
Section: Discussionmentioning
confidence: 99%
“…2001). Study of Huszenicza et al. (2006) showed negative effect of long‐lasting hyperketonaemia in postpartum period on reproductive efficiency in dairy cows.…”
Section: Introductionmentioning
confidence: 99%